KERJASAMA "FRIENDSHIP COOPERATION" SEBAGAI BAGIAN SISTER CITY ANTARA DAEJEON KOREA SELATAN DENGAN TANGERANG SELATAN PERIODE 2015-2019 - Muhammad Raihan Hafiez (2022)
South Tangerang City held a Sister City collaboration with the city of Daejeon. The friendship cooperation started from planning the development of a Smart city in the city of South Tangerang, to the occurrence of the South Tangerang Global Innovation Forum. The friendship cooperation was carried out covering various fields, with the Letter of Intent phase I and also the Letter of Intent phase II or what the South Tangerang City government called the Memorandum of Understanding on friendship cooperation. In carrying out friendship cooperation, until the inauguration of a cooperation agreement between the two regions. The MoU on Friendship Cooperation resulted in several collaborations, both successful such as the Daejeon Youth Exchange Program or unsuccessful/implemented such as the MSME development project. According to the author's initial view, this friendship cooperation cooperation can help improve the performance of the South Tangerang city government and also support the development of South Tangerang City in several aspects, both from the economy, education, and technology. In conducting this research, the author uses descriptive qualitative research methods to analyze the cooperation that has been carried out, and uses several theories and concepts such as paradiplomacy and sister city to help explain the problems that exist in the cooperation between the two cities. In this study, the authors found that the collaboration that started with a smart city was not successful in developing a smart city in South Tangerang. The smart city collaboration between South Tangerang and Daejeon was not successful due to several things, one of which is quite crucial is the lack of communication. From this smart city collaboration, there will be friendship cooperation which will result in the implementation of several things. Then, the implementation of the Memorandum of Understanding friendship cooperation resulted in several topics of cooperation, namely social with the Daejeon student exchange, Economics with the development of a creative economy, the environment with waste sorting, and technology with the development of Smart cities. From these 4 topics, it is known that the successful collaboration is the Daejeon youth student exchange, and also the establishment of the South Tangerang Global Innovation Forum. From the results of this study, it was found that there was a lack of communication from both the South Tangerang City Government and the Daejeon City Government so that cooperation between the two cities was constrained and could only produce a few successful collaborations.